2016
DOI: 10.1186/s12903-016-0220-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the lateral pterygoid muscle on traumatic temporomandibular joint bony ankylosis

Abstract: BackgroundThe pathogenesis of traumatic TMJ ankylosis remains unclear. This study aimed to verify the role of the lateral pterygoid muscle in the pathogenesis of traumatic temporomandibular joint (TMJ) bony ankylosis.MethodsEight 6-month-old male sheep were used in this study. Bilateral TMJ osteotomies were performed to induce sagittal fractures of the mandibular condyle. The lateral one-fourth segment of the disc was removed to establish a model of TMJ bony ankylosis. Subsequently, the function of the left an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Nineteen articles that investigated the pathology of traumatic TMJA were finally included. 4 22 These articles were classified into three groups: predisposing factors and etiological factors, cellular studies, and molecular studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen articles that investigated the pathology of traumatic TMJA were finally included. 4 22 These articles were classified into three groups: predisposing factors and etiological factors, cellular studies, and molecular studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Deng et al. 21 and Liu et al. 22 found that the size of the ankylosed bone mass was reduced after blocking the lateral pterygoid muscles during ankylosis model surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were fed with a standard diet and had free access to water. The traumatic TMJA model was constructed according to the protocol outlined in previous publications (9,11,12). Briefly, the bilateral TMJ capsule was exposed from an incision to the anterior tragus.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the anatomy of the lateral pterygoid muscle (LPM), it can be inferred that the contraction of the LPM will generate sufficient distraction force to the condyle neck during the opening of the mouth and confirm the ‘distraction osteogenesis (DO) effect of LPM’ hypothesis, which is that the LPM may exert a DO effect during the healing of the fractured condyle (7). In addition, the LPM exerts an important function in the reconstruction of the sagittal fractured condyle (8) and a previous study has reported that TMJA will be significantly alleviated if the LPM is dissected (9). Furthermore, the study of Dai et al (10) also suggested that local injection of botulinum toxin A would temporarily block impulses from the LPM's and may effectively prevent the occurrence of traumatic TMJA.…”
Section: Introductionmentioning
confidence: 99%